Amide-linked local anesthetics induce apoptosis in human non-small cell lung cancer - Wang, Hong-Wei; Wang, Le-Yi; Jiang, Li; Tian, Su-Ming; Zhong, Tai-Di; Fang, Xiang-Ming (Journal of Thoracic Disease, 2016)
Background: A retrospective analysis of patients undergoing cancer surgery suggested that using local anesthetics could reduce cancer recurrence and improve survival rate. Previous studies have indicated that local anesthetics may induce apoptosis in several kinds of cells in vitro, but the mechanism is unclear. Methods: Cell viability was analyzed by MTS; reactive oxygen species (ROS), mitochondrial membrane potential (MMP, ∆Ψm), cell cycle distribution, and cell apoptosis assay were detected by flow cytometry; DNA damage was measured by comet assay; cell invasion and migration were observed by microscopy; The expression level of related proteins was detected by western blot assay . Results: The results indicated that lidocaine and ropivacaine could decrease viability, induce G0/G1 phase arrest and apoptosis in human non-small cell lung cancer (NSCLC) cells A549 and H520. Invasion and migration were suppressed. Western blot indicated the related apoptotic pathways proteins changed accordingly. Additionally, lidocaine and ropivacaine downregulated ∆Ψm, provoked DNA damage, upregulated ROS production and activated mitogen-activated protein kinase (MAPK) pathways in A549 and H520 cells. Conclusions: The cytotoxic effect of amide-linked local anesthetics on NSCLC cells were mainly due to apoptosis. The antitumor mechanism of lidocaine and ropivacaine may involve apoptotic pathways and MAPK pathways.